PP.LB03.07: BLOOD-PRESSURE ASSOCIATED VARIANTS IN NPR3 AFFECT HUMAN VASCULAR SMOOTH MUSCLE CELLS PROLIFERATION AND CALCIUM RESPONSE TO ANGIOTENSIN II. (June 2015) - Ren, M.; Ng, F.; Witkowska, K.; Baron, M.; Townsend-Nicholson, A.; Xiao, Q.; Hobbs, A.; Ye, S.; Caulfield, M.J.
Abstract : Objective: A recent genome-wide association study identified a locus within natriuretic peptide receptor C (NPR3) gene to be significantly associated with blood pressure (BP). We aim to functionally characterise the effect of BP- associated SNPs (single nucleotide polymorphisms) at the NPR3 gene locus in the context of BP regulatory pathways. Design and method: Bioinformatic tools, including Encyclopedia of Regulatory DNA Elements (ENCODE), were used to prioritise SNPs for investigation. Primary human umbilical smooth muscle (HUASMCs) and endothelial (HUVECs) cells of different NPR3 genotypes were investigated. Genotype-specific mRNA and protein expression were assessed by qRT-PCR and western blotting, respectively. Open chromatin regions were assayed using formaldehyde-assisted isolation of regulatory elements (FAIRE). Cell proliferation and migration were detected by cell counting and scratch assays. Angiotensin II (AngII)-induced calcium flux was detected using an intracellular fluorescent probe (Calcium 6). Results: The NPR3 risk allele (major allele) in HUASMCs was associated with lower endogenous mRNA (p < 0.001) and protein levels. This was consistent with the intronic SNP rs1173747-minor allele being associated with an open chromatin state (p < 0.01). Furthermore, major-allele expression led to increased cell proliferation (p < 0.05) and calcium response to AngII stimulation (p < 0.05). No difference in migration rates were detected. No such genotype-dependent characteristics were observed in HUVECs. Conclusions: This study has identified potential mechanisms for BP-associated SNPs within NPR3 gene to influence BP predominantly via the vascular smooth muscle.